Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2020)
Dear colleagues, this new issue of our journal is published during difficult times. The second wave of the covid-19 pandemic is here, and it brings new challenges comparable to those encountered during the previous wave. Lockdowns and communicating from a distance are back. We sincerely hope that you and your friends and relatives will remain safe during this time.